Human resources in sports a managerial approach - Tiell, Bonnie; Walton, Kelley (Jones & Bartlett Learning, 2018)
"This book is written for upper-level undergraduate and graduate students pursuing a degree in Sports and Recreation Management, Sports Administration, Coaching, Physical Education, Sports Business, or similar curriculum. Although this will likely be valuable to managers and directors currently working in the sports, recreation, and fitness industry however this is not a market we will actively pursue. Throughout the chapters are examples of forms and documents used by managers and/or human resource specialists in arenas, stadiums, gymnasiums, front offices, fitness centers, golf clubs, bowling alleys, ice rinks, weight rooms, race courses, riding trails, campgrounds, and track complexes. No previous textbook has included the depth of practical applications of human resource tools and activities originating from real professionals with real experience in the field. Each chapter is organized with learning outcomes, an overview of the topic, applicable documents, a summary, key terms, discussion questions, and a global spotlight. The practicality of documented human resource applications and best practices transcends the pages of a textbook designed to engage future and current practitioners in all sectors of sports and recreation." --